THE EFFECT OF THE EARLY INTERVENTION PROGRAM ON DEVELOPMENT OF DEAF INFANTS - Elifcan CESUR (Fırat University, 2019)
Early intervention programs are the programs that aim at minimizing the existing impairments and the effects caused by these impairments by supporting the development of children who have developmental disability or are at risk. Preparing the early intervention programs from the framework of the developmental system approach and the DIR model by emphasizing the titles like early diagnosis, follow-up, individuality, parent-child components and family interaction is highly important in terms of the effectiveness of the program. Based upon this view, in the present study, an early intervention program based on these approaches was applied to a deaf infant and its effect on his developmental process was investigated. In this study using the single-subject research design, the baseline data were obtained and then the early intervention program was applied. During the application of the program, assessments were made at intervals. MEB (Ministry of National Education) Development Observation Form (0-36 months) and the third months later Ages and Stages Questionnaires (ASQ) were used to determine the developmental level at baseline and after the implementation of early intervention program. The early intervention program was weekly administered by the expert to the infant as one-to-one with the participation of the primary caregiver. The program is composed of a total of 32 activities supporting all developmental areas. It was determined that the program had a moderate effect size in the developmental process of the infant. The results of the study revealed that the interactive early intervention program based on the developmental system approach and the DIR model supported the development of the deaf infant, at risk in terms of development.